A Novel Cryptosystem Using Dynamics Perturbation of Logistic Map - Thang, Manh Hoang; Hoang, Xuan Thanh (Old Journal, 2019)
In this paper, a novel cryptosystem is proposed using the method of dynamics perturbation to the Logistic map. The perturbation is carried out by changing the value of its control parameter in bit level after every iteration during encryption and decryption. Consequently, the dynamics of Logistic map becomes non-stationary, and it helps to resist the statistical attacks. Moreover, the key space is expanded significantly. The bit distribution balancing is proposed to have better statistical properties of ciphertext. The example will show the effectiveness of the proposed cryptosystem and the simulation results are compared with those in other works published recently.